A Note on Geology in Relation to Mortality of Fir and Spruce in Chakrata forest Division - Chand, Gulab; Yadav, J. S. P. (Indian Forester, 1970)
Mortality of fir (Abies pindrow) and spruce (Picea smithiana) in Chakrata Forest Division (U.P.) has taken plnce following the heavy fellings carried out during 1941 to 1950. Mention has been made of some of the important observations made by the previous workers. The different geological formations occurring under these forests have been described. An attempt has been made to correlate the mortality of these species with the nature, type and structural features of the underlying rock formations.